2016
DOI: 10.1108/sampj-12-2014-0080
|View full text |Cite
|
Sign up to set email alerts
|

CSR disclosure in response to major airline accidents: a legitimacy-based exploration

Abstract: Purpose-This paper contributes to the literature investigating disclosure reactions to legitimacy threats by analysing the corporate social responsibility disclosure reactions to catastrophic accidents suffered by major airlines. Design/methodology/approach-We use content analysis to examine changes in annual report disclosure in response to four separate airline disasters. We adopt two classification schemes and two measurement approaches to explore these changes. Findings-We find that for three events the or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(72 citation statements)
references
References 27 publications
3
63
0
6
Order By: Relevance
“…Overall, the evidence in this literature is aligned with findings in social and environmental reporting (e.g. Cho, ; Cormier and Magnan, ; Vourvachis et al , ) and suggests that companies modify their behavior when social activists target them (Grolin, ).…”
Section: Theoretical Frameworksupporting
confidence: 78%
“…Overall, the evidence in this literature is aligned with findings in social and environmental reporting (e.g. Cho, ; Cormier and Magnan, ; Vourvachis et al , ) and suggests that companies modify their behavior when social activists target them (Grolin, ).…”
Section: Theoretical Frameworksupporting
confidence: 78%
“…The first two papers are anchored in legitimacy theory and explore, respectively, the use of CSR disclosure during a legitimacy crisis and as a "disguising" strategy. The first contribution by Vourvachis et al (2016) analyses corporate social responsibility disclosure reactions to catastrophic accidents suffered by major airlines. The paper extends the body of research on corporate disclosure reactions to catastrophic events, which has mainly focused on environmental disasters, by considering a broader spectrum of social disclosures.…”
Section: Contributions Of This Special Issuementioning
confidence: 99%
“…The integrate report may have an effect on symbolic legitimacy (Ahmed Haji & Anifowose, 2016) of companies listed on the JSE, especially in terms of providing evidence to the world regarding South Africa"s reporting and corporate governance reforms (Maroun et al, 2014). Academic research has consequently found that corporate annual reports and integrated reports have in cases become merely ceremonial to display companies in the best light (Ahmed Haji & Hossain, 2016;Brennan, Guillamon-Saorin, & Pierce, 2009;Maroun, 2015;Vourvachis, Woodward, Woodward, & Patten, 2016;Williams & Adams, 2013).…”
Section: Theoretical Perspectivementioning
confidence: 99%